(untitled) (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2023)
This research aims to determine the implementation of the National Police Chief’s Circular Letter Number: SE/06/X/2015 concerning Handling Hate Speech and to determine the legal consequences. This research uses empirical research methods, namely research using field data as the main data source, such as the results of interviews and observations. Empirical research is used to analyze law which is seen as patterned behavior in people’s lives which always interact and relate in social aspects. As a result of the research that has been carried out, it was concluded that (1) Polri in carrying out its authority to deal with various hateful behavior speech as regulated in the National Police Chief’s SE also remains subject to general principles of good governance such as being careful and careful in carrying out action, do not abuse authority, and so on. With the National Police Chief’s SE, it should be possible to guarantee enforcement of legal norms is getting better, rather than becoming a cover for arbitrary actions of authorities in controlling the trigger of power. Therefore, internal supervision of the implementers of the circular letter is carried out must run parallel with the authority to implement circular letters the. The National Police Chief also regulates procedures for handling hate incidents speech so as not to cause discrimination, violence or disappearances lives, and/or widespread social conflict. (2) Circular Letter from the Chief of Police placed in a theoretical perspective in state administrative law, products This law is a variant of policy regulations (policy rule) or what in Dutch is called beleidsregel. In state administrative law, state administrative officials (including the National Police Chief) indeed given the authority to issue good legal products in the form of regulations (regeling), state administrative decisions (beschikking), as well as policy regulations. Policy rules are different from a laws or regulations because they are only internally binding to state administration officials themselves and is not intended to be legally binding directly to the community. This is of course different from the law or regulations that must be made following a hierarchical system of regulations legislation and is intended to be externally binding (society) and internally (government officials). Thus, power binding a policy regulation to the community such as the National Police Chief’s SE it is indirect in nature.